The intermediate filament protein nestin serves as a molecular hub for smooth muscle cytoskeletal signaling - Yinna Wang; Guoning Liao; Yidi Wu; Ruping Wang; Dale D. Tang (Respiratory Research, 2023)
Abstract Background The recruitment of the actin-regulatory proteins cortactin and profilin-1 (Pfn-1) to the membrane is important for the regulation of actin cytoskeletal reorganization and smooth muscle contraction. Polo-like kinase 1 (Plk1) and the type III intermediate filament protein vimentin are involved in smooth muscle contraction. Regulation of complex cytoskeletal signaling is not entirely elucidated. The aim of this study was to evaluate the role of nestin (a type VI intermediate filament protein) in cytoskeletal signaling in airway smooth muscle. Methods Nestin expression in human airway smooth muscle (HASM) was knocked down by specific shRNA or siRNA. The effects of nestin knockdown (KD) on the recruitment of cortactin and Pfn-1, actin polymerization, myosin light chain (MLC) phosphorylation, and contraction were evaluated by cellular and physiological approaches. Moreover, we assessed the effects of non-phosphorylatable nestin mutant on these biological processes. Results Nestin KD reduced the recruitment of cortactin and Pfn-1, actin polymerization, and HASM contraction without affecting MLC phosphorylation. Moreover, contractile stimulation enhanced nestin phosphorylation at Thr-315 and the interaction of nestin with Plk1. Nestin KD also diminished phosphorylation of Plk1 and vimentin. The expression of T315A nestin mutant (alanine substitution at Thr-315) reduced the recruitment of cortactin and Pfn-1, actin polymerization, and HASM contraction without affecting MLC phosphorylation. Furthermore, Plk1 KD diminished nestin phosphorylation at this residue. Conclusions Nestin is an essential macromolecule that regulates actin cytoskeletal signaling via Plk1 in smooth muscle. Plk1 and nestin form an activation loop during contractile stimulation.